Can successful pregnancy be achieved and predicted from patients with identified ZP mutations? A literature review - Juepu Zhou; Meng Wang; Qiyu Yang; Dan Li; Zhou Li; Juan Hu; Lei Jin; Lixia Zhu (BMC, 2022)
Abstract Background In mammals, normal fertilization depends on the structural and functional integrity of the zona pellucida (ZP), which is an extracellular matrix surrounding oocytes. Mutations in ZP may affect oogenesis, fertilization and early embryonic development, which may cause female infertility. Methods A PubMed literature search using the keywords 'zona pellucida', 'mutation' and 'variant' limited to humans was performed, with the last research on June 30, 2022. The mutation types, clinical phenotypes and pregnancy outcomes were summarized and analyzed. The naive Bayes classifier was used to predict clinical pregnancy outcomes for patients with ZP mutations. Results A total of 29 publications were included in the final analysis. Sixty-nine mutations of the ZP genes were reported in 87 patients with different clinical phenotypes, including empty follicle syndrome (EFS), ZP-free oocytes (ZFO), ZP-thin oocytes (ZTO), degenerated and immature oocytes. The phenotypes of patients were influenced by the types and location of the mutations. The most common effects of ZP mutations are protein truncation and dysfunction. Three patients with ZP1 mutations, two with ZP2 mutations, and three with ZP4 mutations had successful pregnancies through Intracytoplasmic sperm injection (ICSI) from ZFO or ZTO. A prediction model of pregnancy outcome in patients with ZP mutation was constructed to assess the chance of pregnancy with the area under the curve (AUC) of 0.898. The normalized confusion matrix showed the true positive rate was 1.00 and the true negative rate was 0.38. Conclusion Phenotypes in patients with ZP mutations might be associated with mutation sites or the degree of protein dysfunction. Successful pregnancy outcomes could be achieved in some patients with identified ZP mutations. Clinical pregnancy prediction model based on ZP mutations and clinical characteristics will be helpful to precisely evaluate pregnancy chance and provide references and guidance for the clinical treatment of relevant patients.